Shikonin inhibits gefitinib-resistant non-small cell lung cancer by inhibiting TrxR and activating the EGFR proteasomal degradation pathway. (January 2017) - Li, Xia; Fan, Xing-Xing; Jiang, Ze-Bo; Loo, Wings TY; Yao, Xiao-Jun; Leung, Elaine Lai-Han; Chow, Louis WC; Liu, Liang
Graphical abstract: Abstract: Non-small cell lung cancer (NSCLC) is the dominant type of lung cancer. Molecular targeting has highly improved the treatment efficacy of lung cancer, but new challenges have emerged, such as gefitinib-resistance and cancer recurrence. Therefore, new chemotherapeutic agents and treatment strategies are urgently needed. Shikonin is the main active component of a Chinese medicinal plant 'Zi Cao', which has been shown to exhibit powerful anti-cancer activity in certain types of cancer; however, its activity in gefitinib-resistant lung cancer has never been addressed. In this study, we used a high-throughput screening assay for epidermal growth factor receptor (EGFR) inhibitors and discovered that Shikonin is a potent inhibitor of EGFR. The cytotoxicity of Shikonin and its anti-cancer mechanism in NSCLC was deeply explored. Shikonin exhibited selective cytotoxicity among two NSCLC cell lines (H1975 and H1650) and one normal lung fibroblast cell line (CCD-19LU). Shikonin significantly increased the activity of caspases and poly (ADP-ribosyl) polymerase (PARP), which are indicators of apoptosis, and the intensity of ROS by greater than 10-fold. NAC, an inhibitor of ROS, completely blocked apoptosis, caspase and PARP activation induced by Shikonin. Shikonin remarkably suppressed the phosphorylation of EGFR and led to EGFR degradation. The enhancement of ROS generation in H1650 and H1975 gefitinib-resistant NSCLC cells leads to impairment of growth and induction of apoptosis, whereas modulation of EGFR degradation and its downstream signalling pathways by Shikonin contributes to its anti-tumour properties in H1975 gefitinib-resistant NSCLC cells (with T790M and L858R activating mutations). Shikonin-induced cell apoptosis is closely associated with ROS elevation in the cells. These findings indicate that Shikonin can be an effective small molecule treating gefitinib-resistant NSCLC.